ANALYSIS OF THE APPLICATION OF ACCOUNTING INFORMATION SYSTEMS FOR CASH RECEIPTS AND DISBURSEMENTS AT PT PEGADAIAN SUNGGAL FIELD BRANCH - Nurhikmah, Nabila; Junawan, Junawan; Aliah, Nur (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
This study entitled "Analysis of the Application of Accounting Information Systems to Cash Receipts and Expenditures at PT. Pegadaian Medan Sunggal Branch. This study aims to analyze the application of the cash receipts and disbursements accounting information system by PT. Pegadaian Medan Sunggal Branch and prove whether the accounting information system for cash receipts and disbursements is free from human error. The research on the application of the cash receipts and disbursements accounting information system was carried out using descriptive research methods. Data collection techniques in this study were in the form of observation, interviews, and documentation, the data used were primary data and secondary data. The results of the research that has been done that the application of the accounting information system at the company is quite good in recording cash receipts and disbursements transactions, where this recording system has been carried out systematically on a computer. However, this accounting information system is not free from human error. It is recommended that the application of the accounting information system in the company is carried out better so that it is free from human error.